Hubungan Antara Ibu Hamil Usia ≥ 35 Tahun dengan Kejadian Labioschizis - Yunitasari; Nopi Sani; Arti Febriyani; I Nengah Budiarta (ARTERI : Jurnal Ilmu Kesehatan, 2020)
Abnormalities lip and palate or cleft lip commonly called congenital abnormality or labioschizis is a gap between the right and/or left lip. The incidence of cleft lip with or without cleft palate is one per 700-1000 births worldwide and Asians have the highest risk. Infant death or disability, even the mother died during childbirth in pregnancy aged 35 years and over. Giving birth at the age of 35 years and over, babies who are born susceptible to genetic abnormalities. The purpose of this study was to determine the relationship between maternal age of ≥35 years with labioschizis incident. This study used cross-sectional design: Retrospective, data was collected from the medical records during the period 1 January 2018 to 31 December 2018. The number of samples of 138 respondents, data was analyzed using the chi-square test with a significance level of ρvalue < 0.05. The results showed that most respondents had labioschizis namely 65.9%, while 34.1% of respondents experienced palatoschizis and labiognatoschizis. The lives of most mothers with children experiencing labioschizis are ≥35 years of age is 57.1%. The results of the study there was no correlation between a maternal age ≥ 35 years with the incidence labioschizis with value 0.793 ρvalue means sig >0.05. However, based on the data that researchers get the respondent with maternal age of 35 years tend to have labioschizis, meaning that the older a pregnant woman would be more risk of having babies with labioschizis.